New foliicolous fungi from Indian mangroves (Sunderbans) - A.K. PAL, R.P. PURKAYASTHA and (Indian Phytopathology, 2002)
During a foliicolous fungi survey of Sunderbans mangrove ecosystems 7 fungi were new species. The proposed names for the new species are, Pestalotiopsis bruguierae, P. moluccens, P. heritierae, Cercospora mucronata, Phomopsis xylocarpae, P. sonneratiae and Phyllosticta mangrovei.